DINAMIKA KEHIDUPAN SOSIAL TOKOH UTAMA DALAM NOVEL “DAUN YANG JATUH TAK PERNAH MEMBENCI ANGIN” KARYA TERE LIYE - Ketut Yarsama; Krista Adus (LP3M Universitas PGRI Mahadewa Indonesia, 2021)
The novel The Falling Leaf Never Hates the Wind by Tere Liye tells the social life dynamics of the main character who undergoes social changes in his life. The formulation of the problem in this research is (1) how are the intrinsic elements in the novel Daun Yang Fall Never Hates the Wind by Tere Liye. (2) what is the Social Life Dynamics of the Main Character in Tere Liye's novel The Falling Leaf Never Hates the Wind. This study aims to (1) describe the intrinsic elements in Tere Liye's novel Daun That Falls Never Hates the Wind. (2) to find out the Social Life Dynamics of the Main Character in Tere Liye's novel The Falling Leaf Never Hates the Wind. This study uses the theory of sociology of literature, the theory of changes in social life, and novels. This type of research is descriptive qualitative. The method used in obtaining data is the documentation or library method. The data collection techniques used are recording and carding techniques. The data in this study analyzed qualitatively by using descriptive analysis method. Data presented by informal method. The results of the data analysis show that the intrinsic elements in the novel Daun That Falls Never Hates the Wind by Tere Liye are: The theme contained is the social change in the social life of the main character. The main character is Tania. The setting is in Tania's cardboard house, the neighborhood of Tania's cardboard house, Danar's favorite bookstore, hospital, mother's grave, Danar's rented house, Changi Airport and the largest bookstore in Singapore. The setting of the atmosphere includes joy, fun, pleasure. The plot in this novel is a forward and backward plot. The dynamics of social life in this novel include changes in social life, namely Tania experiencing economic changes so that Tania can continue her schooling. Tania and her sister came out of poverty. Sincere learning and intelligence, Tania was able to graduate from a well-known university in Singapore. Readers are advised to appreciate the novel The Falling Leaf Never Hates the Wind as an afterthought in living social life in society.